Evidence-led adaptive programming: Lessons from MUVA - Sharp, Samuel; Riemenschneider, Nils; Selvester, Kerry (ODI, 2022)
Calls for more ‘adaptive programming’ have been prominent in internati onal development practice for over a decade. Learning-by-doing is a cr ucial element of this, but programmes have often found it challenging to become more learning oriented. Establishing some form of reflective practice, against countervailing incentives, is difficult. Incorporat ing data collection processes that generate useful, timely and practic al information to inform these reflections is even more so.This paper explores MUVA - an adaptive female economic empowerment programme in M ozambique. MUVA, we suggest, is atypically evidence-led. It combines s ystematic, inclusive reflective practice with extensive real-time data collection. We describe the fundamental features of MUVA’s monitoring , evaluation and learning (MEL) approach that supported this. One, how data collection and analysis are synchronised with set cycles for lea rning and adapting projects. Two, how MEL systems are designed to prio ritise actionable learning, with data collection oriented more to the needs of implementing staff than to the reporting requirements of fund ers.This approach was enabled by building collective ownership over th e programme’s objectives and the purpose of MEL from the outset. Imple menters are asked about their motivations, and these are related to th e programme’s Theory of Change. The evidence culture is supported by t he proximity of MEL staff to implementing staff; and through structuri ng upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicators. We conclud e by considering the relevance, or not, of MUVA’s approach to programm es in other contexts or issue areas trying to replicate a similarly ev idence-informed approach to adaptive management. Key messages Learning -by-doing is essential to adaptive programming, but it can be challeng ing to establish data collection processes that generate useful, timel y and practical information. MUVA – a female economic empowerment prog ramme in Mozambique – has an atypically evidence-led adaptive manageme nt approach. This has two fundamental features. One, data collection a nd analysis are synchronised with set cycles for learning and adapting projects. Two, data collection is oriented more to the needs of imple menting staff than to the reporting requirements of funders. Monitorin g, evaluation and learning (MEL) systems are designed to prioritise ac tionable learning. This approach was enabled by building collective ow nership over the programme’s objectives and the purpose of MEL from th e outset. Implementers are asked about their motivations, and these ar e related to the programme’s Theory of Change. The evidence culture is supported by the proximity of MEL staff to implementing staff; and th rough structuring upwards accountability to funders around justifying evidence-based adaptations instead of reporting on more narrow indicat ors.